A visão dos profissionais da educação no contexto do acolhimento e inserção de migrantes venezuelanos nas escolas estaduais de Roraima : estudo de casos - Souzedo, Yves de Carvalho (2021)
The state of Roraima is going through a unique moment in its history: since the year 2015, when the 'crisis' in Venezuela, a country bordering Roraima, has become more acute, that increasingly large numbers of Venezuelan refugees fleeing from hunger, the lack of jobs and so many other problems that plague that country, sought (and continue to seek) in this state of the Brazilian federation a place to live and survive in the face of so many difficulties imposed by life. It is, therefore, a very challenging situation, especially since, on the one hand, many Venezuelans live in a situation of extreme vulnerability, on the other hand, the capacity of local authorities to provide adequate responses to this intensive and concentrated flow of migrants has been shown to be very limited. In this context, the school plays an important role: that of inserting and preparing, both the migrant and the local inhabitant, in this new dynamic, imposed after the intense migratory movement. Thus, the main objective of this research was to analyze how school education has been taking place in the context of the insertion of Venezuelan migrants and the way in which these migrants have been inserted and welcomed in the state public education system of Roraima from the perspective of education professionals (managers and teachers). As specific objectives, it was intended to analyze the performance of the State in this context, as well as to produce data on this reality, through case studies in three schools, the Ana Libória State School (EEAL) and the Monteiro Lobato State School (EEML), located in Boa Vista / RR and the Nova Esperança State School (EENE), located in Vila Samaúma (VS), in the municipality of Mucajaí / RR. To achieve success in the pursuit of objectives, the methodological strategy of qualitative research was used, through readings, application of questionnaires with objective and subjective questions with the management and teaching staff of these schools. The research data revealed positive factors, such as, for example, the fact that Brazilian students tend to welcome Venezuelan students despite all the mass and xenophobic discourse, recurring in Brazil and Roraima and also the fact that several teachers demonstrated in their speeches the willpower and the interest of Venezuelan students in learning and incorporating themselves more fairly in Brazilian society. On the other hand, we saw that most teachers are not prepared to face the situation as they should, but at the same time, the State does not provide the necessary structures and equipment to act in this context. Finally, we conclude that the arrival of Venezuelan students in schools in Roraima brings to reality a new, culturally different and equally virtuous element. The possibilities for actions and practices that can be developed by the school in this context are endless and the school environment will become more fertile and rich. The struggle for public and quality education is the only struggle capable of profoundly transforming society and the only way to combat setbacks.